2013
DOI: 10.3109/0284186x.2013.837582
|View full text |Cite
|
Sign up to set email alerts
|

Palliative pelvic radiotherapy of symptomatic incurable rectal cancer – a systematic review

Abstract: Background.Locally advanced and recurrent rectal cancers frequently cause pelvic morbidity including pain, bleeding and mass effect. Palliative pelvic radiotherapy is used to relieve these symptoms and delay local progression. There is no established optimal radiotherapy regimen and clinical practices vary. Our aim was to review the efficacy and toxicity of palliative pelvic radiotherapy of symptomatic rectal cancer and to evaluate different fractionation schedules, based on published literature.Material and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
56
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 31 publications
2
56
0
Order By: Relevance
“…Considering that short-course regimens with no or low-grade side effects exist, which often improve symptoms such as pain, dyspnea and hemoptysis, clinicians are wary of withholding a meaningful therapeutic measure for patients with terminal cancer (15)(16)(17)(18). Therefore, prediction tools must not predict short survival times in patients who survive long enough to experience a reduced burden of symptoms, and must also identify the majority of patients will succumb to the disease too early to benefit from the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that short-course regimens with no or low-grade side effects exist, which often improve symptoms such as pain, dyspnea and hemoptysis, clinicians are wary of withholding a meaningful therapeutic measure for patients with terminal cancer (15)(16)(17)(18). Therefore, prediction tools must not predict short survival times in patients who survive long enough to experience a reduced burden of symptoms, and must also identify the majority of patients will succumb to the disease too early to benefit from the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients with locally recurrent or primarily inoperable RC may still experience a growing pelvic tumor, potentially leading to symptoms, such as pain, obstruction, and hematochezia [2].…”
mentioning
confidence: 99%
“…Tumor shrinkage in response to radiotherapy is often not apparent radiologically until several weeks after treatment completion [5]. The radiation dose and degree of tumor response required to palliate different pelvic symptoms is unknown, but a recent systematic review of palliative pelvic radiotherapy (PPRT) of RC found symptomatic improvement across a wide range of treatment schedules [2]. Conventional curative fractionation regimens intended to downstage tumors may not be appropriate in the context of symptom palliation, and there is a need for studies evaluating the effects of palliative radiotherapy [6].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a systematic review of the literature, the group of authors behind a prospective study exploring the palliative value of external radiation to 30-39 Gy in 3 Gy fractions, could not find an optimal radiation dose or fractionation useful for palliation [44]. In the prospective study, most patients had major symptomatic relief of the treatment [42].…”
Section: Modifying the Time Interval To Surgerymentioning
confidence: 99%